Abuse of over-the-counter medicines: a pharmacist’s perspective - Sansgiry SS; Bhansali AH; Bapat SS; Xu Q (Dove Medical Press, 2016)
Sujit S Sansgiry, Archita H Bhansali, Shweta S Bapat, Qingqing Xu Pharmaceutical Health Outcomes and Policy, College of Pharmacy, University of Houston, Houston, TX, USA Abstract: Self-care and self-medication practices are essential components of any health care systems. The use of over-the-counter (OTC) medications is a part of the self-medication process. The popularity of OTC medication use among patients may increase the abuse potential of OTC medications. With pharmacists being as accessible as they are, they are often the first line of contact for patients, and have the opportunity to educate and counsel patients on appropriate OTC medication use. The presence of a pharmacist ensures safe and effective use of OTC medications. Pharmacists can liaise with other health care providers in the management of self-care practices by patients. However, a pharmacist has traditionally been underutilized in this role. This article provides a brief review on OTC medications with abuse potential and the effect of self-medication on OTC medication abuse. This review further describes the barriers faced by pharmacists in OTC medication abuse management, given the increased potential of prescription-to-OTC switch in recent years. In addition, the potential for a behind-the-counter drug category to boost patient–pharmacist interaction was discussed. The current review supports the positive role played by pharmacists in the management of OTC medication abuse. This review adds to the knowledge base of the barriers faced by pharmacists to prevent OTC medication abuse while developing appropriate intervention strategies. By expanding the role of pharmacists, OTC medication abuse may be controlled more effectively, thereby providing better patient medication therapy management and outcomes. Keywords: non-prescription, behind-the-counter, medication, self-medication